Mass diffusivity measurements of two cement based materials - HOUNGAN, COMLAN ARISTIDE; AWANTO, CHRISTOPHE; FAGBEMI, LATIF ADÉNIYI; ANJORIN, Malahimi; VIANOU, Antoine (My University, 2015)
The main purpose of a building is to ensure thermal comfort to its occupants. The present work is a contribution to the improvement of the comfort and relates to the characterization of local materials used in Benin. The authors determined the mass diffusivity of the wood composite material and cement-stabilized laterite, as a function of its water content. The experimental device is designed around a magnetic suspension balance. This precision balance can operate without direct contact with the specimen. The temperature and the relative humidity of the measuring chamber rare controlled. The mass of the sample is measured at intervals of 30 s. The diffusivity is obtained from the slope of the transient mass change data. From the analysis of the results, it follows that the cement-stabilized laterite has a mass diffusivity lower than that of the wood composite material. Also, the materials studied can allow the realization of hygrothermic buildings with low cost.
Keywords: Heat; humidity; composite wood-cement; stabilized laterite; slope method; mass diffusivity.